Composite construction in steel and concrete VI : proceedings of the 2008 Composite Construction in Steel and Concrete Conference VI, July 20-24, 2008 [Devil's Thumb Ranch] Tabernash, Colorado - Leon, Roberto T. (American Society of Civil Engineers, 2011)
The sixth in a series, this proceedings contains the 63 technical papers presented at the International Conference on Composite Construction in Steel and Concrete held at the Devil's Thumb Ranch in Tabernash, Colorado, July 20-24, 2008. This book covers a wide variety of topics including composite bridges, composite slabs, shear connectors, composite columns, innovative composite structural systems, fire and seismic resistance of composite structural systems and practical applications. The papers presented in Composite Construction in Steel and Concrete VI represent the state-of-the-art in composite construction worldwide, and will be valuable to structural engineers and anyone involved with composite construction. --